2011
DOI: 10.14748/adipo.v3.273
|View full text |Cite
|
Sign up to set email alerts
|

Leptin stimulates phosphoinositide 3-kinase in the vascular wall: role of ErbB receptors

Abstract: Phosphoinositide 3-kinase (PI3K) phosphorylates phosphatidylinositol 4,5-diphosphate to phosphatidylinositol 3,4,5-triphosphate which then activates multiple intracellular signaling proteins such as protein kinase B (Akt), glycogen synthase kinase-3β, mammalian target of rapamycin (mTOR), etc. PI3K is involved in the regulation of vascular smooth muscle cell contractility, migration and proliferation-processes crucial for the pathogenesis of hypertension, atherosclerosis and restenosis. Increased leptin concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The binding of different Erb-B ligands and the combination of Erb-B homo- and heterodimer receptors can activate distinct downstream pathways, including the mitogen activated protein kinase (MAPK) and the phosphatidylinosithol-3kinase (PI3K) signaling pathways (35), which are able to control cellular behavior by transducing cell signals to the nucleus, then influencing the activity of transcription factors. Based on these assumptions, Beltowski et al have demonstrated the ability of high levels of leptin to transactivate the EGF receptor and activate the receptor Erb-B2 (40). Increased PI3K activity has been observed in the aortic media of adult male Wistar rats exposed to increasing doses of leptin for 10 days, which was markedly attenuated by the EGFR inhibitor AG1478 and by the ErbB2 receptor inhibitor AG825.…”
Section: Role Of Leptinmentioning
confidence: 99%
“…The binding of different Erb-B ligands and the combination of Erb-B homo- and heterodimer receptors can activate distinct downstream pathways, including the mitogen activated protein kinase (MAPK) and the phosphatidylinosithol-3kinase (PI3K) signaling pathways (35), which are able to control cellular behavior by transducing cell signals to the nucleus, then influencing the activity of transcription factors. Based on these assumptions, Beltowski et al have demonstrated the ability of high levels of leptin to transactivate the EGF receptor and activate the receptor Erb-B2 (40). Increased PI3K activity has been observed in the aortic media of adult male Wistar rats exposed to increasing doses of leptin for 10 days, which was markedly attenuated by the EGFR inhibitor AG1478 and by the ErbB2 receptor inhibitor AG825.…”
Section: Role Of Leptinmentioning
confidence: 99%